Evaluation of Alternative Diagnostic Techniques for Diagnosis of Cerebral Malaria in a Tertiary Referral Hospital in Bangladesh - Hossain, MA; Afroj, S; Rahman, MR; Yunus, EB; Samad, R; Asna, ZH; Akter, S; Faiz, MA (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):180-5. The abstract of this article is available on the PubMed website